2008
DOI: 10.1016/j.molcel.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Cancer Stem Cell Marker USP22 Is a Subunit of the Human SAGA Complex Required for Activated Transcription and Cell-Cycle Progression

Abstract: Polycomb genes encode critical regulators of both normal stem cells and cancer stem cells. A gene signature that includes Polycomb genes and additional genes coregulated with Polycomb genes was recently identified. The expression of this signature has been reported to identify tumors with the cancer stem cell phenotypes of aggressive growth, metastasis, and therapy resistance. Most members of this 11 gene signature encode proteins with well-defined roles in human cancer. However, the function of the signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
505
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(529 citation statements)
references
References 66 publications
12
505
2
Order By: Relevance
“…As the subunit of the human SAGA coactivator complex, USP22 is linked to the regulation of gene transcription by deubiquitinating histones H2A and H2B (2,3). In addition, USP22 deubiquitinates intracellular protein, including the shelterin protein telomeric repeat binding factor 1 (4), the histone deacetylase sirtuin 1 (5) and the far upstream element-binding protein 1 fructose-1,6-bisphosphatase 1 (4), and therefore performs an extensive physiological function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the subunit of the human SAGA coactivator complex, USP22 is linked to the regulation of gene transcription by deubiquitinating histones H2A and H2B (2,3). In addition, USP22 deubiquitinates intracellular protein, including the shelterin protein telomeric repeat binding factor 1 (4), the histone deacetylase sirtuin 1 (5) and the far upstream element-binding protein 1 fructose-1,6-bisphosphatase 1 (4), and therefore performs an extensive physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…USP22 has been indicated in tumorigenesis. Deletion of USP22 leads to the accumulation of cells in the G 1 phase of the cell cycle (2). For these reasons, USP22 is a putative cancer stem cell marker.…”
Section: Introductionmentioning
confidence: 99%
“…87 USP22 is required for full activation of certain p53 and Myc target genes in human fibroblasts, and is required for malignant transformation by the latter ( Table 1). 89 Contrary to these findings, a recent study found that knockdown of USP22 resulted in an increase in the basal expression of p53 and its target p21 in a bladder cancer cell line, possibly as a result of a decrease in expression of Mdm2, a negative regulator of p53. 88 This may be indicative of the effect of additional mutations in the cancer cell line used, highlighting the need for all findings to be confirmed in a variety of genetic backgrounds.…”
Section: Fundamental Questionsmentioning
confidence: 84%
“…All of them deubiquitylate both H2A and H2B, although H2A is more preferentially targeted (Zhang, 2003). MYSM1, USP7, USP22 and BRCC36 are part of the 2A-DUB, polycomb-repressive complex 1, SAGA and BRCA1-A multisubunit complexes, respectively (Zhu et al, 2007a;Zhang et al, 2008;Feng et al, 2010;Maertens et al, 2010). Nevertheless, USP3 and USP16 have not been found in any of these complexes, suggesting that their chromatin-regulatory mechanisms may be different.…”
Section: Chromatin Remodelingmentioning
confidence: 99%